(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores the formation of historical thinking through national heritage and education. The study analyzes the role of cultural traditions, historical memory, spiritual values, and educational processes in developing students’ historical consciousness and critical thinking skills. Special attention is paid to the importance of integrating national heritage into educational curricula in order to strengthen patriotic feelings, national identity, and respect for historical values among young people. The article also highlights innovative pedagogical approaches and modern educational technologies that contribute to the effective development of historical thinking in contemporary education.